GABA‐like immunoreactivity in Biomphalaria: Colocalization with tyrosine hydroxylase‐like immunoreactivity in the feeding motor systems of panpulmonate snails. Issue 11 (6th May 2018) - Vaasjo, Lee O.; Quintana, Alexandra M.; Habib, Mohamed R.; Mendez de Jesus, Paola A.; Croll, Roger P.; Miller, Mark W.
Abstract: The simpler nervous systems of certain invertebrates provide opportunities to examine colocalized classical neurotransmitters in the context of identified neurons and well defined neural circuits. This study examined the distribution of γ‐aminobutyric acid‐like immunoreactivity (GABAli) in the nervous system of the panpulmonates Biomphalaria glabrata and Biomphalaria alexandrina, major intermediate hosts for intestinal schistosomiasis. GABAli neurons were localized in the cerebral, pedal, and buccal ganglia of each species. With the exception of a projection to the base of the tentacle, GABAli fibers were confined to the CNS. As GABAli was previously reported to be colocalized with markers for dopamine (DA) in five neurons in the feeding network of the euopisthobranch gastropod Aplysia californica (Díaz‐Ríos, Oyola, & Miller, 2002), double‐labeling protocols were used to compare the distribution of GABAli with tyrosine hydroxylase immunoreactivity (THli). As in Aplysia, GABAli‐THli colocalization was limited to five neurons, all of which were located in the buccal ganglion. Five GABAli‐THli cells were also observed in the buccal ganglia of two other intensively studied panpulmonate species, Lymnaea stagnalis and Helisoma trivolvis . These findings indicate that colocalization of the classical neurotransmitters GABA and DA in feeding central pattern generator (CPG) interneurons preceded the divergence of euopisthobranch and panpulmonate taxa. These observations also support the hypothesis that heterogastropod feeding CPG networks exhibit a common universal design. Abstract : GABA‐like immunoreactivity (magenta) and tyrosine hydroxylase‐like immunoreactivity (green) in the anterolateral quadrant of the cerebral ganglion of the pulmonate snail, Biomphalaria glabrata . Species of Biomphalaria are the major intermediate hosts for Schistosoma mansoni, the trematode worm that causes the most widespread from of schistosomiasis.